1991
DOI: 10.1073/pnas.88.11.4641
|View full text |Cite
|
Sign up to set email alerts
|

Serodiagnosis of hepatitis C virus (HCV) infection with an HCV core protein molecularly expressed by a recombinant baculovirus.

Abstract: An enzyme-linked immunosorbent assay (ELISA) was developed for serological diagnosis of hepatitis C virus (HCV) infection, using HCV core protein (p22) synthesized by a recombinant baculovirus. Among 58 clinically well-defined chronic non-A, non-B hepatitis (NANBH) patients, 49 (84.5%) were positive for p22 antibody (anti-p22), whereas 42 (72.4%) were positive for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
2

Year Published

1992
1992
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(57 citation statements)
references
References 29 publications
3
52
2
Order By: Relevance
“…Patients were from St. Marianna Hospital, Kawasaki, Kanagawa; Tokyo National Chest Hospital, Kiyose, Tokyo; and Shinshu University School of Medicine, Nagano. 12,13 Informed consent was obtained from all patients, and the study had the approval of the Ethical Committees of the hospitals. To study the natural history of acute non-A non-B hepatitis, serial sera samples had been collected over many years and maintained at Ϫ20°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were from St. Marianna Hospital, Kawasaki, Kanagawa; Tokyo National Chest Hospital, Kiyose, Tokyo; and Shinshu University School of Medicine, Nagano. 12,13 Informed consent was obtained from all patients, and the study had the approval of the Ethical Committees of the hospitals. To study the natural history of acute non-A non-B hepatitis, serial sera samples had been collected over many years and maintained at Ϫ20°C.…”
Section: Methodsmentioning
confidence: 99%
“…11 This assay is used as a surrogate test to estimate the level of HCV-neutralizing (NOB) antibodies. Here we report on the serum antibody responses to HCV structural proteins in a rare group of patients who spontaneously resolved chronic hepatitis C. 12,13 We have found that the appearance and maintenance of high serum titers of NOB antibodies in the course of chronic hepatitis C is accompanied by virus clearance and clinical resolution of liver disease.…”
mentioning
confidence: 99%
“…Each well of the ELISA plates (ICN-Flow Laboratories) was coated with 50 p.1 of the antigen solution for 16 h at 4 °C. Human sera were analysed for anti-E2 Ab by ELISA using the coated antigens as described (Chiba et al, 1991). Western blotting.…”
Section: Methodsmentioning
confidence: 99%
“…Chiba et al (1991) and Matsuura et al (1992) have reported that p22 and gp35 produced in insect cells infected with recombinant 0001-0959 © 1992 SGM baculovirus carrying cDNAs of the corresponding genome regions were detected by sera from NANBH patients. Thus, it is suggested that p22 and gp35 are the mature viral proteins existing in cells of patients infected with HCV.…”
Section: Introductionmentioning
confidence: 99%